CORRELATION BETWEEN GLYCATED HAEMOGLOBIN LEVELS AND RANDOM BLOOD GLUCOSE - Kazmi, Nasir Hussain Shah; Gillani, Saima; Afzal, Saleem; Hussain, Saad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Glycated haemoglobin or glycosylated haemoglobin (HbA1c) is a form of haemoglobin that is measured primarily to identify the average plasma glucose concentration over prolonged periods of time. Levels of HbA1c represent the average blood glucose levels of diabetic patients over the previous 120 days. The objective of this study was to see the correlation between HbA1c levels and random glucose levels. Methods: This descriptive study included 106 randomly selected patients with known diabetes from the outpatients department. Random sugar levels were measured by using venous blood samples. HbA1c levels were measured in venous blood by BIO-RAD D-10 HPLC Method. Data were recorded on a proforma. Pearson’s correlation was applied to find out any significant correlation between the glycated haemoglobin levels and the random blood glucose levels. Results were plotted on simple scatter plot and p<0.01 was considered significant. Conclusions: A significant linear positive correlation exists between levels of HbA1c and random blood sugar. Keywords: Diabetes, HbA1c, blood glucose levels, HbA1c